Benefits management : delivering value from IS & IT investments - Ward, John, 1947- (Wiley, 2006)
"Benefits Management: Delivering Value from IS & IT Investments provides a comprehensive explanation of how organizations can achieve greater success in realizing the benefits of their investments in IS and IT and other major change programmes. It incorporates the latest knowledge from research with real examples from the use of the approach in a wide range of organizations. It will prove valuable and informative to business managers and IS/IT professionals as well as academics and students."--Jacket.